Luteolin Induces Apoptosis, G0/G1 Cell Cycle Growth Arrest and Mitochondrial Membrane Potential Loss in Neuroblastoma Brain Tumor Cells - Wang, F.; Gao, F.; Pan, S.; Zhao, S.; Xue, Y. (Drug Research, 2015)
The objective of the present research work was to evaluate the anticancer properties of luteolin against SH-SY5Y neuroblastoma tumor cell line. Cell viability was evaluated by MTT assay after luteolin treatment. Lactate dehydrogenase assay (LDH) was used to evaluate the extent of cell death induced by luteolin. Flow-cytometry was used to examine the effect of luteolin on cell cycle progression and mitochondrial membrane potential (ΛΨm) in SH-SY5Y cells. Phase-contrast microscopy detected the morphological changes in SH-SY5Y cells after luteolin treatment. Our results demonstrated that luteolin induced dose-dependent as well as time-dependent growth inhibition of SH-SY5Y cells with IC50 value of 27.1 µM after 12 h of incubation. Further, luteolin induced significant release of LDH from SH-SY5Y cell cultures following luteolin treatment significantly at 25 and 50 µM doses which corresponds to significant cell death. Phase-contrast microscopy revealed characteristic morphological features of apoptosis induced by luteolin. Flow-cytometry revealed that luteolin induced G0/G1 cell cycle growth arrest in SH-SY5Y cells. Luteolin also induced a progressive and dose-dependent reduction in the mitochondrial membrane potential. In conclusion, our results revealed that luteolin significantly induces growth inhibition of SH-SY5Y tumor cells by inducing apoptosis accompanied with G0/G1 cell cycle growth arrest and concomitant loss in mitochondrial membrane potential (ΛΨm). As such luteolin can be developed as a potent anticancer agent against brain tumor disorders.
Keywords: Luteolin; apoptosis; cell-cycle; anticancer activity